Analisis Faktor-Faktor Yang Memengaruhi Utang Luar Negeri dan Dampaknya Terhadap Pertumbuhan Ekonomi Indonesia - Fathoana, Alif; Kamaruddin, Citra Aini; Alam, Syamsu (Journal Management & Economics Review (JUMPER), 2024)
This study aims to analyze the influence of each Budget Deficit, Rupiah Exchange Rate (Exchange Rate), and Foreign Exchange Reserves on Indonesia's Foreign Debt, and to determine the impact of foreign debt on Indonesia's economic growth(GDP). The type of data used is a time series from 2013-2023. Secondary data in the form of Budget Deficit (Rupiah), GDP (Total % of GDP), Rupiah Exchange Rate (against the US Dollar) and Foreign Exchange Reserves (Billion Rupiah). The analysis method used to analyze the data in this study uses multiple linear regression analysis and simple regression. The results of this study indicate that the Budget Deficit has a positive but insignificant effect on Indonesia's Foreign Debt during the 2013-2023 period. This shows that the increase in the amount of the budget deficit results in an increase in foreign debt but the amount is small so it is categorized as not real. The Rupiah Exchange Rate (Exchange Rate) has a positive but insignificant effect on Indonesia's Foreign Debt during the 2013-2023 period. This shows that the increase in the US Dollar exchange rate results in an increase in foreign debt but the amount is small so it is categorized as unreal. Foreign Exchange Reserves have a positive but insignificant effect on Indonesia's Foreign Debt during the 2013-2023 period. This shows that the increase in the amount of foreign exchange reserves results in an increase in foreign debt but the amount is small so it is categorized as unreal. Foreign debt has a positive and significant impact on Indonesia's economic growth (GDP) during the 2013-2023 period. This shows that the increase in the amount of foreign debt results in a real increase in economic growth. The results of the study show that 86.9% of Foreign Debt can have a positive impact on Indonesia's Economic Growth, while the remaining 13.1% is influenced by other variables outside the study.